(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The purpose of modern education is the formation of an individual possessing comprehensive knowledge, new outlook on the future, and creative thinking. The formation cognitive competence of the students, their desire to strengthen their independence is the basic requirement for the improvement of the level of teacher’s educational activity in a comprehensively new direction. This article is dedicated to the methods of developing students’ cognitive skills, as well as the ways of improving the educational process at lessons of Kazakh language. Moreover, a special attention should be paid to the use of innovative technologies in the educational process in order to achieve good results in activation of cognitive activity of the students. As teaching is a special type of cognitive activity, works carried out in this direction is dedicated to the development of the competences of the students.